Судостроительный аспект развития арктической транспортной системы - Volostnykh, Vadim; Ivankovich, Anna Vadimovna (Administrative Consulting, 2025)
The article examines the needs and opportunities of the sectoral potential for the development of the Arctic zone of the Russian Federation. The goals, objectives and indicators (indicators) of achieving the goals and the success of the tasks are defined, and a forecast of the main outcomes of Strategy 2035 is drawn up.